A Concise Synthesis of the Key Tetrahydrofuran Moieties of Caruifolin A and EBC‐342. Issue 44 (5th June 2020) - Fernandes, Rodney A.; Bethi, Venkati
Abstract : A common strategy for the concise synthesis of the key tetrahydrofuran moieties of caruifolin A and EBC‐342 is presented. Asymmetric dihydroxylation and intramolecular SN 2‐cyclization are key strategic reactions for the synthesis of the furan fragments. Abstract : A common strategy for the synthesis of substituted tetrahydrofuran moieties of caruifolin A and EBC‐342 has been developed based on asymmetric dihydroxylation and intramolecular SN 2‐cyclization.